2012
DOI: 10.1093/ijpor/eds024
|View full text |Cite
|
Sign up to set email alerts
|

Own Culture First? Nationalism and the Preference for National Cultural Goods

Abstract: The following full text is a publisher's version.For additional information about this publication click this link. http://hdl.handle.net/2066/121237Please be advised that this information was generated on 2024-07-22 and may be subject to change. Article 25fa End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act. This article entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…Items referring to being proud of ‘The Dutch performance in sports’, ‘The Dutch achievements in art and literature’ and ‘The Dutch history’ load on one factor. In line with previous research – arguing that patriotism refers to love for and pride of one’s nation (Blank and Schmidt, 2003; Coenders et al, 2004; Dekker et al., 2003) also with particular regard for national cultural aspects (Meuleman et al., 2013) – we interpret this factor as cultural patriotism (ranging from 1 ‘not proud at all’ to 4 ‘very proud’) (Cronbach’s α = .69). The second factor, relating to chauvinism , consisted of two items: ‘It would be a better world if people from other countries were more like the Dutch’ and ‘Generally speaking, the Netherlands is a better country than most other countries’ (ranging from 1 ‘totally disagree’ to 5 ‘totally agree’).…”
Section: Methodssupporting
confidence: 60%
“…Items referring to being proud of ‘The Dutch performance in sports’, ‘The Dutch achievements in art and literature’ and ‘The Dutch history’ load on one factor. In line with previous research – arguing that patriotism refers to love for and pride of one’s nation (Blank and Schmidt, 2003; Coenders et al, 2004; Dekker et al., 2003) also with particular regard for national cultural aspects (Meuleman et al., 2013) – we interpret this factor as cultural patriotism (ranging from 1 ‘not proud at all’ to 4 ‘very proud’) (Cronbach’s α = .69). The second factor, relating to chauvinism , consisted of two items: ‘It would be a better world if people from other countries were more like the Dutch’ and ‘Generally speaking, the Netherlands is a better country than most other countries’ (ranging from 1 ‘totally disagree’ to 5 ‘totally agree’).…”
Section: Methodssupporting
confidence: 60%
“…Other studies (Cleveland et al, 2009; see also Meuleman et al, 2012) have shown that cosmopolitan attitudes clearly shape consumer behavior; those who are more cosmopolitan buy more exotic goods and more luxury goods. A stringent theoretical explanation for the relationship between cosmopolitan identity and cosmopolitan consumption could be based on symbolic interactionist identity theory, which assumes that individuals try to uphold and strengthen certain aspects of their identity through meaningfully related forms of behavior (Stryker and Burke, 2000).…”
Section: Determinants Of Cosmopolitan Consumptionmentioning
confidence: 93%
“…According to Hussaini (2020), history can build a society's identity. According to Meuleman, Bekhuis, Lubbers, and Scheepers (2013), the culture of a society or nation can strengthen the nationalism of nefara citizens, especially the younger generation. Similar to Setyawan and Saddhono (2018), Cannigia (2015), and Prahastiwi (2014), they have Ceprotan performing art performed the sendratari (dramatic dancing art) telling the story of Ki Godeg and Dewi Sekar journies with developing the Sekar Village.…”
Section: Discussionmentioning
confidence: 99%